Paradoxical fate and biological action of peroxynitrite on human platelets. - Moro, M A (1994)
Peroxynitrite (ONOO-), which is formed from the reaction of nitric oxide (NO) and superoxide (O2-), has been suggested to be responsible for some of the cytotoxic effects of these molecules. When protonated, ONOO- gives rise to hydroxyl (OH.) and nitrogen dioxide (NO2) radicals, which are capable of inducing tissue damage. We have investigated the effects of ONOO- on human platelets in vitro in order to explore the potential of this oxidant to contribute to tissue damage. ONOO- caused aggregation of washed platelets and reversed the inhibition of aggregation induced by S-nitroso-N-acetyl-DL-penicillamine (SNAP), prostacyclin, and indomethacin. However, in platelet-rich plasma, ONOO- not only did not possess proaggregatory properties but acted as an inhibitor of platelet aggregation. This reversal of the aggregatory effect of ONOO- could also be achieved in washed platelets by adding low concentrations of plasma, human serum albumin, or glutathione and was inhibited by hemoglobin. An analysis of the reaction products of ONOO- and glutathione revealed the presence of both NO and S-nitrosoglutathione in quantities sufficient to account for the antiaggregatory effects observed. Thus the fate and therefore the actions of ONOO- in biological systems are critically dependent on the biological environment in which this oxidant is present.